Life history of Colpomenia sinuosa (Scytosiphonaceae, Phaeophyceae) in the Azores. - Toste, Marisa F. (2003)
Colpomenia sinuosa (Mertens ex Roth) Derbès and Solier (Scytosiphonaceae, Phaeophyceae) is a common species on the rocky intertidal shores of the Azores, where reproductive gametophytes occur throughout the year. Life-history studies of this species were carried out in culture, and both sexual and asexual reproduction were observed. Anisogamous gametes fused to form zygotes. The zygotes gave rise to a filamentous prostrate sporophyte generation bearing unilocular sporangia, under both short-day and long-day conditions at 15 and 22° C, and to both unilocular and plurilocular sporangia, under the lower temperature condition. Unispores developed into gametophytes, and plurispores gave rise to filamentous sporophytes. Asexual reproduction was carried out by unfused female gametes and asexual plurispores produced from the same gametophyte. Unfused gametes developed into filamentous prostrate sporophytes producing unilocular sporangia in both culture conditions, and unispores released from the sporangia gave rise to gametophytes. Asexual plurispores from field gametophytes, under both culture conditions, developed directly into new gametophytes. The species exhibited three types of life history: a heteromorphic, diplohaplontic; a heteromorphic, monophasic (both with alternation between the erect and filamentous prostrate thalli); and a monomorphic, monophasic.